Tingkat Pengetahuan Mahasiswa Profesi Ners Angkatan 25 Universitas Muhammadiyah Surakarta tentang Penyakit HIV/AIDS - Dhimas Lanang Wicaksono; Adisty Rose Artistin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the level of knowledge of class 25 nursing professional students at Muhammadiyah University of Surakarta regarding HIV/AIDS. The method used is descriptive research with a survey research design. The research results showed that of the 95 respondents, 65 people had a good level of knowledge (68.4%), 27 people had a sufficient level of expertise (28.4%), and three people had a poor level of understanding (3.2%). In conclusion, most students of the 25th batch of nursing profession students at Muhammadiyah University of Surakarta regarding HIV/AIDS have good knowledge. Keywords: HIV/AIDS, Students, Knowledge